Relationship of Mycotoxins Accumulation and Bioactive Components Variation in Ginger after Fungal Inoculation - Yang, Zhixin; Wang, Haiwei; Ying, Guangyao; Yang, Meihua; Nian, Yujiao; Liu, Jiajia; Kong, Weijun (Frontiers in Pharmacology, 2017)
Ginger has got increasing worldwide interests due to its extensive biological activities, along with high medical and edible values. But fungal contamination and mycotoxin residues have brought challenges to its quality and safety. In the present study, the relationship of content of mycotoxins accumulation and bioactive components variation in ginger after infection by toxigenic fungi were investigated for the first time to elucidate the influence of fungal contamination on the inherent quality of ginger. After being infected by Aspergillus flavus and Aspergillus carnonariu for different periods, the produced mycotoxins was determined by an immunoaffinity column clean-up based ultra-fast liquid chromatography coupled with tandem mass spectrometry, and the main bioactive components in ginger were analyzed by ultra performance liquid chromatography-photodiode array detection. The results showed that consecutive incubation of ginger with A. flavus and A. carnonariu within 20 days resulted in the production and accumulation of aflatoxins (especially AFB1) and ochratoxin A, as well as the constant content reduction of four bioactive components, which were confirmed through the scanning electron microscope images. Significantly negative correlation was expressed between the mycotoxins accumulation and bioactive components variation in ginger, which might influence the quality and safety of it. Furthermore, a new compound was detected after inoculation for six days, which was found in our study for the first time.